Sistem Pengendalian Suhu pada Kandang Ayam Broiler menggunakan PID Controller - Bagas Gerry Caesario; Eko Setiawan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The most influential factor in broiler chicken coop farms is the ambient temperature. If the temperature is too humid, the temperature of the cage environment will rise so that broiler chickens feel hot and have difficulty breathing. Conversely, if the chicken coop is too dry, broiler chickens will feel cold compared to the temperature in the environment, which will affect productivity. The sistem that build using Fan Dc and Heater Lamp as actuator to raise temperature and lower temperature. This research is aimed at overcoming this problem by controlling the temperature of the broiler chicken coop. The parameter used in this research is temperature. The research uses the PID controller method to assist the system in controlling the temperature of the broiler chicken coop. The temperature sensor used is the DHT22, which has the advantage of digital signal output and a wider range of temperature measurements. The method used is PID, which controls the rotation of the motor for the fan, namely proportional control, which has a fast rise time, integral control to minimize errors, and derivative control to reduce overshoot and undershoot. The test results showed that testing the accuracy of the DHT22 temperature and humidity sensors compared to the hygrometer resulted in an average temperature reading error of 0.87%, based on testing the lowest PWM value, resulting in a value of 60 on the DC fan and 25 on the lamp dimmer, as well Kp : 4, Ki : 0.2, Kd : 1 gives the most optimal system response with steady state value : 27.9963, steady-state error : 0.004, settling time : 33962, overshoot : 0.01%, these values are the smallest test values of among other tests so that it shows that test 2 provides the most optimal system response.